Pigmentation of skin - Scott, Glynis (Henry Stewart Talks, 2014)
Pigmentation of human skin is a complex process, Basic building blocks of normal skin pigmentation, The nature of melanin and the regulation of melanin synthesis by the enzyme tyrosinase, The cellular unit of melanin synthesis: the melanocyte, The molecular basis of tanning, The evolutionary pressures and gene associations linked to the human distinctive global pigmentation phenotype.